2014
DOI: 10.1017/s1751731114000470
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-embryo interaction leading up to the initiation of implantation of pregnancy in cattle

Abstract: Early embryo development following fertilization occurs in the oviduct. However, despite being the site of fertilization in cattle, it is possible to by-pass the oviduct by producing embryos in vitro and/or by transferring blastocysts recovered from one female into the uterus of another. While there is substantial evidence for the oviduct having an influence on the quality of the developing embryo, manifested in altered morphology, gene expression and cryotolerance, evidence for a two-way dialogue is weak. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 57 publications
1
66
1
4
Order By: Relevance
“…In particular, concentrations of PGF 2 α normally exceed several times that of PGE 2 (Bartol et al, 1981;Lewis et al, 1982;Shelton et al, 1990;Ulbrich et al, 2009). At such stages, PGs activate a number of IFNT-stimulated genes, and it seems that PGs could be important recognition signalling molecules in cattle (Spencer et al, 2013;Lonergan and Forde, 2014). In contrast with these observations later in development, our results in blood on Day 8 showed that ZE embryos did not affect PGE 2 concentrations.…”
Section: Discussioncontrasting
confidence: 92%
“…In particular, concentrations of PGF 2 α normally exceed several times that of PGE 2 (Bartol et al, 1981;Lewis et al, 1982;Shelton et al, 1990;Ulbrich et al, 2009). At such stages, PGs activate a number of IFNT-stimulated genes, and it seems that PGs could be important recognition signalling molecules in cattle (Spencer et al, 2013;Lonergan and Forde, 2014). In contrast with these observations later in development, our results in blood on Day 8 showed that ZE embryos did not affect PGE 2 concentrations.…”
Section: Discussioncontrasting
confidence: 92%
“…Regulation of the synthesis and release of PGE 2 and PGF 2α are crucial to this process (Bazer 2013, Lonergan & Forde 2014. Failure of PR is a significant risk factor for embryonic mortality (Diskin et al 2011, Forde et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Following successful ovulation and subsequent fertilisation, production of interferon-τ (IFNT) by the trophectoderm begins at around day 8 of gestation and increases dramatically during conceptus elongation (Kimura et al 2004). A sufficient threshold level of IFNT must be reached by day 16 to ensure pregnancy recognition (PR) and prevention of luteolysis (Forde et al 2011, Lonergan & Forde 2014. IFNT acts in a paracrine manner on the uterine endometrium to develop a receptive environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lonergan and Forde (2014) conclude that while there is substantial evidence for the oviduct having an influence on the quality of the developing embryo, evidence for a two-way dialogue is weak. However, successful growth and development of the posthatching blastocyst and pregnancy establishment are a result of the two-way interaction between a competent embryo and a receptive uterine environment.…”
mentioning
confidence: 89%